THEORETICAL AND METHODOLOGICAL APPROACHES TO THE ANALYSES OF THEUNIVERSITY`S CONCEPTUAL MODELS - Кузьменко, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
It is analyzed different methodological approaches to the study of the University`s idea; it is formulated the main theoretical and methodological bases of study of the University`s conceptual models; it is distinguished their structural components; it is grounded the necessity to study the phenomenon of the University in the context of the main historical types of rationality.